Chinese Investors, Labour Discipline and Developmental Cosmopolitanism. Issue 6 (4th November 2013) - Pál, Nyíri
ABSTRACT: In recent years, China has emerged as a major source of investment and development assistance across the 'developing world', triggering the rise of global networks that in some ways stand apart from the existing order of globalization. This article, based on ethnographic fieldwork and interviews in Cambodia from 2009 to 2011, begins to explore the significance of Chinese investors and managers, a new globe‐trotting elite involved in projects around the world. Understanding how this new Chinese mobile class sees its mission is crucial for making sense of how China's 'rise' may be re‐scripting globalization and, specifically, how it may be offering new visions of modernity. The author's research suggests that Chinese investors and managers engage in a developmental discourse which is reminiscent partly of colonial days and partly of the heyday of post‐war developmentalism. This discourse articulates the possibility and necessity of progress imposed by outside actors, and is accompanied by measures that inculcate a strict Fordist labour discipline. At the same time, the author argues, it may also contain the seeds of a new developmental cosmopolitanism.